Factors associated with discharge on higher respiratory support for children with tracheostomy hospitalized with bacterial tracheostomy‐associated infections: A prospective, multicenter cohort study - Krystal S. Jin; Naoko Kono; Jonathan D. Cogen; Sarah Hofman DeYoung; Catherine S. Forster; Andrea Hahn; Margaret Rush; John M. Morrison; Joanna E. Thomson; Sukhada V. Mairal; Michael N. Neely; Wendy J. Mack; et al. (Journal of Hospital Medicine, 2026)
Abstract We conducted a multicenter prospective cohort study to identify factors associated with discharge on higher respiratory support in children with tracheostomy hospitalized for bacterial tracheostomy‐associated infections (bTRAINs). We included children 0–21 years with tracheostomy hospitalized for bTRAIN at six freestanding children's hospitals between 2020 and 2024. The primary outcome was discharge on higher respiratory support compared to pre‐hospital baseline. Generalized linear mixed‐effects regression models accounted for patient and hospital clustering. We included 641 children representing 1180 hospitalizations, with a median age of 5 years; 45.9% were female, 35.6% Hispanic, and 20.0% Non‐Hispanic Black. 24.7% were discharged on higher respiratory support. In adjusted analyses, discharge on higher respiratory support was associated with increased oxygen requirement, escalation of chronic ventilator settings, acute ventilatory support, and longer length of stay. In our study, discharge on higher respiratory support was driven by illness severity, rather than demographic or home support factors.